Study of Spirometra Egg by Scanning Electron Microscopy: Operculum and Operculum Suture at one End - Kavana, Nicholas Jairo (Research Perspectives of Microbiology and Biotechnology Vol. 3, 2024)
Spirometra is a zoonotic parasite. An egg is the first stage in the life cycle of Spirometra species. It can be used in the identification of Spirometra species. Spirometra eggs were collected from the faeces of experimentally infected cats. The eggs collected were used for morphological studies using light microscope and scanning electron microscope (SEM). Eggs collected from faeces of cats were fixed in 4% Glutaraldehyde, then post fixed in 1% Osmium tetroxide, dehydrated in ethanol series. Dehydrated material was dried to a critical point with carbon dioxide in a Polaron Critical Point Dry (CPD 7501). The dried material was mounted on aluminium stubs. The specimen was gold-coated in a sputter coater (B10-RAD). Then eggs were examined in a Philips SEM 515. Scanning electron microscopy (SEM) images revealed the presence of operculum and operculum suture at one end of the egg.